2020
DOI: 10.1002/ame2.12145
|View full text |Cite
|
Sign up to set email alerts
|

A murine model of dengue virus infection in suckling C57BL/6 and BALB/c mice

Abstract: Dengue is a significant public health concern across tropical and subtropical regions worldwide, principally causing disease in children. Very young children are at increased risk of severe manifestations of dengue infection. The mechanism of dengue disease in this population is not fully understood. In this study, we present a murine model of dengue virus primary infection in suckling C57BL/6 and BALB/c mice in order to investigate disease pathogenesis. Three‐day‐old C57BL/6 mice intraperitoneally infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Almost all the parameters did not change significantly. Moreover, the levels of lactate dehydrogenase activity, red blood cell counts, hemoglobin concentration, mean corpuscular hemoglobin concentration, and hematocrit are in the normal BALB/c ranges. The changes in white blood cell and monocyte counts are slight, and less than 15% exceed the higher limits of the normal levels . Thus, we concluded that the nanoparticles should not have any relevant side effects.…”
Section: Resultsmentioning
confidence: 98%
“…Almost all the parameters did not change significantly. Moreover, the levels of lactate dehydrogenase activity, red blood cell counts, hemoglobin concentration, mean corpuscular hemoglobin concentration, and hematocrit are in the normal BALB/c ranges. The changes in white blood cell and monocyte counts are slight, and less than 15% exceed the higher limits of the normal levels . Thus, we concluded that the nanoparticles should not have any relevant side effects.…”
Section: Resultsmentioning
confidence: 98%
“…We verified the role of vimentin in DENV invasion in SV129 suckling mice with and without vimentin knockout. Many models have been used to study DENV, including A/J ( Shresta et al., 2004 ), BALB/c ( Ahmad et al., 2019 ), C57BL/6 ( Byrne et al., 2020 ), and AG129 ( Tan et al., 2010 ) mice for dengue virus tropism and pathogenic research; the DENV-infected non-human primate ( Kayesh and Tsukiyama-Kohara, 2022 ), AG129 mouse continuous infection, cross-infection-established ADE mouse models to study the immune mechanisms of DENV infection ( Blaney et al., 2002 ); and DENV-infected suckling mouse ( Pelliccia et al., 2017 ) and DENV-infected SCID mouse models in vaccine research. In this study, we used suckling mice because adult mice displayed no obvious clinical signs after infection, and DENV-2 was not detected in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected daily postinfection for viremia detection 6 . Viral RNA was extracted using the NucleoSpin® RNA Virus and quantified by quantitative reverse‐transcription PCR (qRT‐PCR) using an ABI StepOnePlus TM real‐time PCR system.…”
Section: Methodsmentioning
confidence: 99%